Multisensory integration, brain plasticity and optogenetics in visual rehabilitation - Martina Lucchesi; José Fernando Maya-Vetencourt; Dario Rusciano (Frontiers in Neurology, 2025)
Multisensory integration enables the brain to integrate information from different sensory modalities while enhancing perception. This principle relies on phenomena of neuroplasticity (i.e., the ability of neuronal networks in the brain to adapt to changing environmental conditions) and is crucial for visual rehabilitation, particularly in hemianopia and retinal degeneration. Here we review emerging experimental approaches and their translational potential for vision recovery in visually impaired patients. Rehabilitation strategies incorporating multisensory training, optogenetics, and pharmacological interventions have demonstrated to be instrumental in restoring visual function by leveraging plasticity of inputs from different sensory modalities. Emerging technologies such as virtual reality and auditory–visual stimulation further optimize neural reorganization. Future research should focus on refining these interventions to enhance sensory compensation and recovery. Understanding the role of multisensory ganglion cells and retinal circuits may unlock new strategies for improving visual function in visually impaired individuals.